2004
DOI: 10.1160/th03-09-0554
|View full text |Cite
|
Sign up to set email alerts
|

Elevated coagulation factor VIII and the risk for recurrent early pregnancy loss

Abstract: Inherited and acquired thrombophilia are associated with recurrent pregnancy loss. Recently, an increased risk for thromboembolic disease was described for patients with elevated coagulation factor VIII, but it is unknown whether there is also an association to early pregnancy loss. We therefore evaluated the relation between recurrent early pregnancy loss and levels of coagulation factor VIII. We enrolled 49 unrelated Caucasian women with a history of 2-6 early pregnancy losses and 48 healthy controls, who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 26 publications
5
29
1
1
Order By: Relevance
“…The strongest association of thrombophilia with RPL was observed with protein S deficiency. These data seem to be in agreement with the results of several studies [7,14,17,18]. Marietta et al [18], in their study, evaluated statistically significant association (p = 0.0002) between elevated factor VIII level and early pregnancy failures.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The strongest association of thrombophilia with RPL was observed with protein S deficiency. These data seem to be in agreement with the results of several studies [7,14,17,18]. Marietta et al [18], in their study, evaluated statistically significant association (p = 0.0002) between elevated factor VIII level and early pregnancy failures.…”
Section: Discussionsupporting
confidence: 89%
“…A number of studies have reported an increased risk of RPL in women with inherited thrombophilia [5][6][7]. In the European prospective cohort study on thrombophilia (EP-COT), a significant association between thrombophilia and miscarriage was reported [8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, new evidence seems to be available for the role of increased maternal plasma levels of clotting factor VIII and the risk of RPL [53]. Furthermore, acquired activated protein C resistance, which is not associated with …”
Section: Acquired Thrombophiliamentioning
confidence: 99%
“…Elevated levels of FVIII and FX could lead to hypercoagulability. Factor VIII is a component of the intrinsic coagulation pathway and is associated with the risk of venous thrombosis 13 and increases during a normal pregnancy. 7 Factor X is a vitamin K-dependent plasma glycoprotein that plays a pivotal role in the coagulation cascade, because it is the first enzyme in the common pathway of thrombin formation.…”
Section: Hemostatic Variables In Healthy Pregnant Women and Pregnant mentioning
confidence: 99%